The impact of the Eurosystem's covered bond purchase programme on the primary and secondary markets - John Beirne; Lars Dalitz; Jacob Ejsing; Magdalena Grothe; Simone Manganelli; Fernando Monar; Benjamin Sahel; Matjaž Sušec; Jens Tapking; Tana Vong (European Central Bank (ECB), 2011)
This paper provides an assessment of the impact of the covered bond purchase programme (hereafter referred to as the CBPP) relative to its policy objectives. The analysis presented on the impact of the CBPP on both the primary and secondary bond markets indicates that the Programme has been an effective policy instrument. It has contributed to: (i) a decline in money market term rates, (ii) an easing of funding conditions for credit institutions and enterprises, (iii) encouraging credit institutions to maintain and expand their lending to clients, and (iv) improving market liquidity in important segments of the private debt securities market. The paper also provides an overview of the investment strategy of the the Eurosystem with regard to the CBPP portfolio.
Keywords: E22; L63; L86; O3; O47; 330; covered bonds; liquidity; primary market; secondary market; Pfandbrief; Offenmarktpolitik; Euromarkt; EU-Staaten